FAKTOR PENYEBAB PENGHAPUSAN DANA TALANGAN HAJI DI BANK SYARIAH INDONESIA (Studi Kasus ex BNI Syariah Indralaya) - Ahmad Ichsan; Choirunnisak Choirunnisak; Meriyati Meriyati (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri Palembang, 2021)
This research was motivated when the policy of eliminating hajj bailouts was lowered, it made researchers want to know the factors of eliminating hajj bailouts at Bank Syariah Indonesia (BNI Syariah Indralaya), as well as how the solutions for customers provided by Bank Syariah Indonesia (BNI Syariah Indralaya) related to the elimination of hajj bailouts. This study aims to analyze the abolition of hajj bailouts at Bank Syariah Indonesia (BNI Syariah Indralaya). This research is descriptive using a qualitative approach. This research data uses primary data. To explore relevant data, the writer uses the interview method, after the data has been collected, it is analyzed using descriptive analysis. The results showed that the elimination of hajj bailouts was due to hajj bailouts that were not the main product, hajj bailout products were not profitable, and the high waiting list for prospective hajj pilgrims. The solution provided by the bank is the introduction of the iB Hasanah Savings product.